Effect of Filler Metal Selection on Microstructure and Hardness of MIL-DTL 46100E Armor Steel Welded by Gas Metal Arc Welding (GMAW) - Setiawan, Anang; Imastuti, Imastuti; Puspita, Maura Indah (International Journal of Mechanical Computational and Manufacturing Research, 2025)
Welding is one of the manufacturing processes widely used in engineering fields such as vehicles, bridges, and others, including in the construction of combat vehicles (military) that have special materials with high hardness (Armor Steel). This study examines the effect of filler type on the welding process on the microstructure and hardness of MIL-DTL 46100E Armor Steel using the Gas Metal Arc Welding (GMAW) method. The fillers used were ER-110, ER-307, and ER-70S.  The tests were carried out using metallographic analysis to study microstructural changes in the Weld Metal (WM) and HAZ areas and Vickers hardness testing. Macro testing results showed that the ER-307 filler produced a wider weld zone, while ER-70S produced a narrower weld zone. Microstructure testing revealed that ER-307 produced a finer and more stable structure, with a predominance of pearlite and ferrite phases in the Weld Metal and martensite in the HAZ. Hardness test results show that ER-307 has the highest hardness in the WM area at 411.9 HV and in the HAZ (501.6 HV), followed by the lowest hardness produced by the ER-70S filler at 297.5 HV and an HAZ value of 500 HV. Overall, ER-307 demonstrated the best performance for welding MIL-DTL 46100E steel, with stable hardness and optimal microstructure throughout the weld zone. This study provides guidance in selecting filler for welding armor steel, which can be applied to the development of combat vehicle technology.